Sheep meat consumers in Mexico: Understanding their perceptions, habits, preferences and market segments - Alanís, P.J.; Miranda-de la Lama, G.C.; Mariezcurrena-Berasain, M.A.; Barbabosa-Pliego, A.; Rayas-Amor, A.A.; Estévez-Moreno, L.X. (Meat science, 2022)
Sheep meat is an essential element within the multicultural mosaic of Mexican agri-food traditions. A total of 332 consumers were surveyed face-to-face in restaurants specializing in selling traditional sheep meat products. Our results showed that consumers could be segmented based on their perceptions, habits, and preferences towards sheep meat. For consumers, sheep meat is perceived as food with unique sensory attributes, coming from healthier animals than other species and traditional characters. Their willingness to pay extra is subject to the guarantee that the meat is safe, free of hormones and antibiotics, and to a lesser extent, certified organic. The multivariate analysis suggested three clusters or consumer profiles named passive, wholehearted, and deep-rooted, which explained the associations among attitudes, some demographic variables, and consumption frequency. The nascent national sheep meat industry needs to consider these concerns in developing marketing and trust strategies to attract, maintain, and build loyalty among Mexican consumers.